The Lucy flyby of (52246) Donaldjohanson: A bilobed asteroid with tumbling rotation - Simone Marchi; Harold F. Levison; Keith S. Noll; John R. Spencer; Thomas S. Statler; Olivier S. Barnouin; James F. Bell; Edward B. Bierhaus; Richard Binzel; William F. Bottke; Daniel Britt; Michael E. Brown; et al. (Science, 2026)
The main belt asteroid (52246) Donaldjohanson (DJ) is a likely member of the Erigone asteroid family. This implies that DJ is a fragment of a larger parent body that was destroyed in a collision about 155 million years ago. We report observations taken during a flyby of DJ by the Lucy spacecraft. We found that DJ is composed of two heavily cratered lobes, connected by a smoother neck, with overall dimensions 8.8 kilometers (km) by 4.4 km by 3.1 km. The crater density is consistent with the Erigone family’s age, except for craters <0.4 km, which have been preferentially erased. DJ rotates slowly in a tumbling state, likely owing to spin-down by radiative forces. Surface spectra show iron-bearing phyllosilicates, indicating moderate aqueous evolution on the parent body.